Penerapan Etika Bisnis Islam di Rumah Makan Berkah Banjar - Dwi Ariyati; Fadila Oktiana Sari; Lilis Renfiana (International Forum of Researchers and Lecturers, 2024)
Application of Islamic Business Ethics or RM. Berkah Banjar 38, the subject of this research. Researchers use qualitative research methods. Qualitative research methods provide descriptive data in the form of spoken and written words and observable behavior. Therefore, researchers obtain three components: data reduction, data presentation, and data validation. R.M. Based on research, Berkah Banjar 38 applies business ethics. We provide the best products and services to meet customer needs. We offer the best, fastest, most accurate service at prices commensurate with the quality of our products. Engage in healthy competition. Collaborate to maintain integrity. Below are examples of business ethics that can be applied and are consistent with Islamic business ethics. Providing halal products and setting prices based on these products